Circular Thinking In A Technological Age: Designing For A Regenerative Future - Berawi, Mohammed Ali; Miraj, Perdana; Sari, Mustika (CSID Journal of Infrastructure Development, 2025)
Architecture, engineering, and construction sector is experiencing challenges related to environment and economic aspects. It consumes vast amounts of resources and energy and contributes heavily to global carbon emissions. Academics and industry leaders are trying to explore various strategies to combat climate change by shifting toward circularity. It is a systems-based approach that prioritizes regenerative design, responsible consumption, and closed-loop resource use. At the heart of this shift lies the interplay between circularity, technology, and the environment that can reshape how we live, produce, and consume. But this transformation is not simply about adopting greener practices; it’s about rethinking the role of innovation in creating systems that can sustain our lives. Circular economy (CE) is not just a sustainability trend; it is an emerging as a smart business model that balances environmental responsibility with sufficient profitability. It challenges businesses and cities alike to ask: how can we design products that are repairable, cities that are resource-aware, and systems that regenerate rather than deplete? Just as "brainware" is central to the success of smart cities, CE demands informed decision-makers, consumers, and designers who can navigate complexity and rethink waste as opportunity. By rethinking material flows and closing resource loops, CE offers a practical alternative to the outdated "take, make, dispose" mindset. Robust policy and legal frameworks for implementing the economic system by providing incentives and mitigating barriers are required to be issued by government, as well as business industries need to produce added value via eco-friendly products and services, and positive behaviors. Technology that is combined with circular principles has the potential to accelerate our transition toward more sustainable living. Advanced technologies in the past years have make it easier for people to achieve towards circular transformation. For instance, Internet of Things allow us to give digital life to physical objects, tracking them from creation to disassembly. Artificial Intelligence can then analyze this information to find the best ways to repair, remanufacture, or recycle them. These tools are incredibly powerful, but they are just tools. They have no purpose or direction without human guidance. Their ultimate success depends entirely on how people choose to use them. Technology solutions can be used to integrate CE principles from the design to the operation stages. The technological revolution has made it possible to transform entire systems of production, management, and governance into more effective and efficient systems. CE is not built by technology but a combination of different roles from the people. It is driven by human who think about a product’s second and third life before it is even made. It is shaped by business leaders who have the courage to shift from selling disposable units to providing durable services. It is guided by policymakers who create rules that make it easier and more profitable to reuse materials than to discard them. And it is powered by a skilled workforce that can operate the advanced systems required for remanufacturing and recycling. CE and technology cannot function without the active participation of its citizens. By placing humanity at the core of this vision, we ensure that we are not just building a more efficient system, but a more resilient, equitable, and prosperous world. CE is not built by technology but a combination of different roles from the people. It is driven by human who think about a product’s second and third life before it is even made. It is shaped by business leaders who have the courage to shift from selling disposable units to providing durable services. It is guided by policymakers who create rules that make it easier and more profitable to reuse materials than to discard them. And it is powered by a skilled workforce that can operate the advanced systems required for remanufacturing and recycling. CE and technology cannot function without the active participation of its citizens. By placing humanity at the core of this vision, we ensure that we are not just building a more efficient system, but also a more resilient, equitable, and prosperous world.